2022
DOI: 10.1128/aac.00646-22
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Beta-Lactam Antibiotics with and without Therapeutic Drug Monitoring in Patients with Pseudomonas aeruginosa Pneumonia or Bloodstream Infection

Abstract: This objective of this study was to compare clinical outcomes in hospitalized patients with Pseudomonas aeruginosa pneumonia (PNA) or bloodstream infection (BSI) receiving beta-lactam antibiotic (BLA) infusions with and without the guidance of therapeutic drug monitoring (TDM). A retrospective, parallel cohort study was conducted at two academic medical centers between December 2015 and January 2020, UF Shands Gainesville, which uses BLA TDM for select patients (BLA TDM), and UF Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…In two studies, the PK/PD target was 100% f T > 4xMIC 16 , 18 . In another publication, both 100% f T > MIC and 100% f T > 4 × MIC were considered as targets, and no sufficient data were provided for the comparison group that could have allowed their extraction 19 . In three publications, multiple PK/PD targets were employed 20 22 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies, the PK/PD target was 100% f T > 4xMIC 16 , 18 . In another publication, both 100% f T > MIC and 100% f T > 4 × MIC were considered as targets, and no sufficient data were provided for the comparison group that could have allowed their extraction 19 . In three publications, multiple PK/PD targets were employed 20 22 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data on clinical cure from the infection were extracted from five studies including 616 patients 15 19 . Significantly higher odds of clinical cure were identified in the intervention group in the analysis of the pooled results [OR 2.22; 95% CI 1.78–2.76; I 2 = 0%], as well as in the subgroup analysis of the observational studies [OR 2.10; 95% CI 1.47–3.00; I 2 = 0%] and of the randomized controlled trials [OR 2.58; 95% CI 1.60–4.15; I 2 = 0%, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 A recent retrospective study with 31% obese patients (BMI > 30 kg/m 2 ) in the cohort demonstrated a benefit in clinical outcomes with β-lactam TDM versus no TDM and controlled for obesity. 23 Cefepime and piperacillin-tazobactam were the most commonly used β-lactams in both cohorts for treatment…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 95%
“…European guidelines and workgroups have recommended that TDM be routinely performed when β‐lactam antibiotics are used in critically ill patients, but include no recommendations for dosing in obesity 21,22 . A recent retrospective study with 31% obese patients (BMI > 30 kg/m 2 ) in the cohort demonstrated a benefit in clinical outcomes with β‐lactam TDM versus no TDM and controlled for obesity 23 . Cefepime and piperacillin–tazobactam were the most commonly used β‐lactams in both cohorts for treatment of P. aeruginosa pneumonia or bloodstream infection.…”
Section: Review Of Specific Antimicrobial Agentsmentioning
confidence: 99%